Rosmarinic Acid Alleviates Radiation-Induced Pulmonary Fibrosis by Downregulating the tRNA N7-Methylguanosine Modification-Regulated Fibroblast-to-Myofibroblast Transition Through the Exosome Pathway - Zhang T; Mi J; Qin X; Ouyang Z; Wang Y; Li Z; He S; Hu K; Wang R; Huang W (Dove Medical Press, 2024)
Tingting Zhang,1- 3,* Jinglin Mi,1- 3,* Xinling Qin,1- 3,* Zhechen Ouyang,1- 3 Yiru Wang,1- 3 Zhixun Li,1- 3 Siyi He,1- 3 Kai Hu,1- 3 Rensheng Wang,1- 3 Weimei Huang1- 3 1Department of Radiation Oncology, the First Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi, People's Republic of China; 2Guangxi Key Laboratory of Immunology and Metabolism for Liver Diseases, Nanning, Guangxi, People's Republic of China; 3Key Laboratory of Early Prevention and Treatment for Regional High-Frequency Tumors (Guangxi Medical University), Ministry of Education, Nanning, Guangxi, People's Republic of China*These authors contributed equally to this workCorrespondence: Weimei Huang; Rensheng Wang, Department of Radiation Oncology, the First Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi, People's Republic of China, Email huangweimei@gxmu.edu.cn; wangrensheng@gxmuhospital.cnBackground: Radiation-induced pulmonary fibrosis (RIPF) is a common complication after radiotherapy in thoracic cancer patients, and effective treatment methods are lacking. The purpose of this study was to investigate the protective effect of rosmarinic acid (RA) on RIPF in mice as well as the mechanism involved.Methods: m7G-tRNA-seq and tRNA-seq analyses were conducted to identify m7G-modified tRNAs. Western blotting, immunohistochemistry, northwestern blotting, northern blotting, immunofluorescence, wound-healing assays and EdU experiments were performed to explore the molecular mechanism by which RA regulates fibroblast-to-myofibroblast transformation (FMT) by affecting the exosomes of lung epithelial cells. Ribo-seq and mRNA-seq analyses were used to explore the underlying target mRNAs. Seahorse assays and immunoprecipitation were carried out to elucidate the effects of RA on glycolysis and FMT processes via the regulation of 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase 3 (PFKFB3) acetylation.Results: We found that RA had an antifibrotic effect on the lung tissues of RIPF model mice and inhibited the progression of FMT through exosomes derived from lung epithelial cells. Mechanistically, RA reduced the transcription and translation efficiency of sphingosine kinase 1 in lung fibroblasts by decreasing N7-methylguanosine modification of tRNA, downregulating the expression of tRNAs in irradiated lung epithelial cell-derived exosomes, and inhibiting the interaction between sphingosine kinase 1 and the N-acetyltransferase 10 protein in fibroblasts. Furthermore, the acetylation and cytoplasmic translocation of PFKFB3 were reduced by exosomes derived from irradiated lung epithelial cells, which following RA intervention. This suppression of the FMT process, which is triggered by glycolysis, and ultimately decelerating the progression of RIPF.Conclusion: These findings suggest that RA is a potential therapeutic agent for RIPF.Keywords: rosmarinic acid, exosomes, tRNA, N7-methylguanosine, radiation-induced pulmonary fibrosis